If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 1 = 3x + 8 Reorder the terms: 1 + 5x = 3x + 8 Reorder the terms: 1 + 5x = 8 + 3x Solving 1 + 5x = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 1 + 5x + -3x = 8 + 3x + -3x Combine like terms: 5x + -3x = 2x 1 + 2x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 1 + 2x = 8 + 0 1 + 2x = 8 Add '-1' to each side of the equation. 1 + -1 + 2x = 8 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 8 + -1 2x = 8 + -1 Combine like terms: 8 + -1 = 7 2x = 7 Divide each side by '2'. x = 3.5 Simplifying x = 3.5
| x+-4=-8 | | -7x-16=-3x-12 | | 5x-11=-2x+31 | | 8x+13=11x-23 | | 24t-.8t^2=90 | | 6x-15=12x+20 | | 5r+3r=10 | | x^3+4x-2=0 | | 24t-8t^2=90 | | 9x+3x-10=3(3x+1) | | 8x^2+29x+15= | | 2/10= | | 4x^2-12x+45=0 | | 12x-17=6x+25 | | x^3+2x^2=520 | | Isy=2x-3 | | (x^2)-2x+1=0 | | 18+-(18)= | | -2x-3=-7 | | ln(x-2)+ln(x+2)=ln(2x+11) | | 4x^2-23x+39=2x+3factorize | | 27j-6=17j+7 | | 4x-2=9x-3 | | 2y+12=4y-4 | | 12+10=5a+7-8a | | 4t-6=6t+12 | | x^3+2x^2-520=0 | | 4x+7=8x-7 | | ln(x)=3-ln(2x) | | 53+34= | | 34+X=87 | | 2x^2+8x-5x-20=0 |